Mitigation of Power System Oscillation in a DFIG-Wind Integrated Grid: A Review - Theophilus Ebuka Odoh; Aliyu Sabo; Noor Izzri Abdul Wahab (Applications of Modelling and Simulation, 2022)
The continuous rise in demand for power supply has made researchers and power system engineers seek alternatives through renewable energy sources to complement the power supply in the power system grid. Wind energy conversion system (WECS) which is the means of harnessing power generation through wind is reportedly one of the most widely installed renewable alternative sources globally. Integrating WECS into the conventional power system grid results in a complex power system grid. Thus, during a disturbance or a fault period on the grid, if proper control measures are not put in place, power system instability due to power system oscillations arises. One such control measure is the damping controller which is coupled to the generating plant through its excitation system. Damping controllers help to dampen power system oscillations, but due to the dynamic nature of the power system and uncertainties inherent in a wind-integrated power grid system, fixed damping controller parameters cannot effectively dampen power system oscillations. Hence, damping controller design becomes an optimization problem. This research reviews damping controller design in a wind-integrated system using optimization techniques.